PENDEKATAN SISTEM DALAM PENDIDIKAN - Adnan Adnan (Fakultas Tarbiyah, Universitas Ibrahimy, 2018)
In principle, everything on earth has own systems. Those systemsare required by all beings on this earth. There are various elements in the education system such as: goals, students, management, structure and schedule, materials, teachers, facilities and infrastructure, media, technology, quality control, education costs, and etc. All these elements are interrelated and supportive each one and another. If the system in education can be likened to a computer, then every component has the duties and functions that support each other. The National Education System in Indonesia is a very complex education system,because there are various elements and a series of input-process-output that affect each other internally. While externally, the National Education System influenced by politics, economic, socio-cultural, defense-security aspects as well as various stakeholders related to education.